SEORANG PENDERITA ENDOKARDITIS INFEKTIF AKIBAT INFEKSI CATHETER DOUBLE LUMEN PADA PASIEN HEMODIALISIS - Aditya Purwaka (Jurnal Medika Hutama, 2022)
The use of catheter double lumen (CDL) to deliver hemodialysis treatment may be associated with some problems.The most serious problems is infection . This complication impacts morbidity and mortality and has emerged as the primary barrier to long-term catheter use. Bacteremia is the most serious type of infection associated with catheter use. It can result in metastatic infection and even lead to death of the patient. Prophylaxis is important to decrease the risk of infection. The use of an antibiotic ointment at the exit site until it has healed and the long-term use of a dressing to cover the exit site are effective in decreasing the incidence of exit-site infection. With optimal catheter use management, it should be possible to reduce the incidence of catheter related bacteremia (CRB) to a level in the range of 1 ⁄ 1000 catheter days. Antibiotic locking solutions show promise and may, if verified in appropriate clinical studies, prove to be important adjuncts to the management of catheter.In this case, between blood culture and CDL culture have the same result of organism.